Risk Factors Of The Occurrence Complications Of Severe Pre-Eclampsia At Public Hospital Of Datu Sanggul In 2022-2023 - Padila, Risa; Hipni, Rubiati; Yuniarti, Yuniarti; Lailid, Fitria Jannatul (Jurnal Riset Kesehatan, 2025)
The maternal mortality rate in Tapin Regency was the highest in South Kalimantan Province in 2022 (MMR= 303/100,000 KH) and 2023 (MMR= 287/100,000 KH) dominated by preeclampsia as the highest cause. Datu Sanggul Hospital has the highest number of maternal deaths, 16 out of 20 maternal deaths in 2022-2023. The purpose of this study was to determine the relationship between risk factors that affect the occurrence of severe pre-eclampsia complications at the Public Hospital of Datu Sanggul in 2022-2023.. This study used an observational analytic method with a case-control design and simple random sampling technique. Samples in this study were 90 respondents, 45 with Severe Pre Eclampsia with complications and 45 without complications. The dependent variables were maternal age, parity, gestational age, multiple pregnancies, obesity, hypertension history, and diabetes mellitus history taken from secondary data. Statistical analysis used was chi-square and odds ratio. The results showed that there was a significant relation between hypertension history on the occurrence of Severe Pre Eclampsia complications (p-value 0.034) and a risk of 2.737 times to experience Severe Pre Eclampsia with complications. There is no significant relationship between maternal age (p-value 1,000), parity (p-value 0,395), gestational age (p-value 0,199), multiple pregnancies (p-value 0,361), obesity (p-value 1,000), diabetes mellitus history (p-value 0,352) on the occurrence of Severe Pre Eclampsia complications at Public Hospital of Datu Sanggul in 2022-2023. In conclusion, Hypertension history is a variable that has a significant relation to the occurrence of Severe Pre Eclampsia complications.